Infectious Complications of Mucositis in Postchemotherapy Neutropenic Cancer Patients: Three Case Reports and a Review of the Literature. Issue 5 (September 2019) - Shah, Neepa; Adashek, Jacob J.; Molinas, Natalia L.; Ramsakal, Asha; Greene, John N.
Abstract : Abstract: Mucositis is a common, painful, and potentially dangerous adverse effect of many chemotherapy regimens. The mucosal barrier can be compromised from oncologic therapies resulting in high levels of exposure to organisms. These are often normal flora that become opportunistic pathogens, especially in these patients who already have compromised cellular immunity from neutropenia and humoral immunity from cytotoxic agents. The combination of a hampered immune system along with breakdown of the mucosa can lead to severe infections and lead to complications that undermine patient outcomes. The most common types of infections that are seen in neutropenic patients are bacterial, followed by viral, and then fungal. This case series will outline 3 vignettes of patients who developed mucositis secondary to chemotherapy-induced neutropenia and will review the most common infections seen in this delicate patient population plus empiric treatment strategies. For this review, a literature search was made using Google Scholar Database. Key words searched included bacterial, fungal, viral, mucositis, and leukemia . Articles published between 1983 and 2018 were selected.